Density of freshly fallen snow in the central Rocky Mountains - Judson, Arthur, author; Doesken, Nolan, author; Colorado Climate Center, Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1999)
New snow density distributions are presented for six measurement sites in the mountains of Colorado and Wyoming. Densities were computed from daily measurements of new snow depth and water-equivalent from snow board cores. All data were measured in wind-protected forest sites. Observed densities of freshly fallen snow ranged from 10 kg m-3 to 257 kg m-3. Average densities at each site based on four years of daily observations ranged from 72 to 103 kg m-3. Seventy-two percent of all daily densities fell between 50 and 100 kg m-3. Approximately 5% of all daily snows had densities below 40 kg m-3. The highest frequency of low densities occurred at Steamboat Springs and Dry Lake. Density distributions from a few other sites in the U.S. appear very similar to these Rocky Mountain distributions except that the frequency of densities greater than 100 kg m-3 are significantly greater west of Colorado and Wyoming. The relationship between air temperature and new snow density exhibited a decline of density with temperature but an r value of only 0.52. No obvious reversal toward higher densities occurred at cold temperatures as some previous studies have reported. No clear relationship was found between snow density and the depth of new snowfalls. Correlations of daily densities between measurement sites decreased rapidly with increasing distance between sites. New snow densities are strongly influenced by orography which contributes to large density differences over short distances.
September 1999.
Keywords: Snow -- Rocky Mountains; Snow surveys -- Rocky Mountains